Reducing the Cut-Off Value of the Fecal Immunochemical Test for Symptomatic Patients Does Not Improve Diagnostic Performance - Navarro, Mercedes; Hijos, Gonzalo; Sostres, Carlos; Lué, Alberto; Puente-Lanzarote, Juan Jose; Carrera-Lasfuentes, Patricia; Lanas, Angel (Frontiers in Medicine, 2020)
Introduction. The faecal immunochemical test (FIT) has been established as a cost-effective test in colon cancer screening programmes. This test could also be helpful in symptomatic patients prior to colonoscopy, but data about diagnostic performance and accurate cut-off values for these patients are still scarce. Methods. Prospective study that included consecutive unselected patients with gastrointestinal symptoms referred for colonoscopy between November 2016 and June 2018. We performed a FIT (FOB Gold® test, cut-off 20 micrograms of Hb/gram of faeces) prior to colonoscopy and determined the accuracy of FIT in terms of sensitivity, specificity, positive and negative predictive value for clinically significant pathology, advanced neoplasia and colorectal cancer in symptomatic patients, using two different cut-off values. Results. A total of 727 patients (44.3% men, aged 58.5 ± 14.9 years) was included in the study. The main symptom was history of previous (non-active) rectal bleeding (34.7%), followed by diarrhoea (15.0%). Over one quarter of the patients (25.9%) had a positive FIT result. The caecal intubation rate was 95.5%. Clinically significant pathology was identified in 142 colonoscopies (19.5%), advanced neoplasia in 115 (15.8%) and colorectal cancer in 36 colonoscopies (5.0%). FIT performed very well for clinically significant pathology, advanced neoplasia and cancer, with a high negative predictive value (NPV). Reducing the cut-off value to 10 μg/g yielded similar NPV results, with a decrease in specificity. Using a combination of symptoms with a positive FIT result did not improve FIT performance. Only specificity was slightly higher compared to FIT alone, but this was paralleled by a decrease in sensitivity and NPV for cancer and clinically significant pathology. The odds of presenting clinically significant pathology, advanced neoplasia or cancer increased with FIT concentration. Conclusions. The specificity and NPV of FIT for clinically significant pathology, advanced neoplasia and cancer are high in symptomatic patients. FIT is a helpful test for determining the need to perform further studies. It may not be necessary to reduce the cut-off value for symptomatic patients, since FIT performance with the current standard cut-off value used in colorectal cancer screening was accurate. FIT can be used to avoid or prioritise colonoscopy procedures.